Effect of nitrogen and glyphosate on the plant community composition in a simulated field margin ecosystem: Model-based ordination of pin-point cover data. (15th December 2022) - Damgaard, Christian; Strandberg, Beate; Ehlers, Bodil; Hansen, Rikke Reisner; Strandberg, Morten Tune
Abstract: The effect of nitrogen and glyphosate on the plant community composition was investigated in a simulated field margin ecosystem. The plant community composition was inferred from pin-point cover data using a model-based ordination method that is suited for modelling pin-point cover data. The mean structure of the ordination model is analogous to a standard linear model, which enabled us to estimate the mean effects of nitrogen and glyphosate and their interaction in the two-dimensional ordination space. There were significant effects of both nitrogen and glyphosate on the plant community composition and overall species diversity. The effects of nitrogen and glyphosate on the plant community composition differed significantly. Furthermore, the estimated combined effects of nitrogen and glyphosate indicated that nitrogen and glyphosate enforced the effect of each other on the plant community composition by synergistic interactions. Addition of nitrogen and glyphosate was found to favor a plant community that was dominated by perennial grasses, and there was a tendency for glyphosate to select for plant communities in which annual plants were more frequent. The results suggest that using the notion of plant functional types and specific knowledge of the degree of glyphosate tolerance may be effective for predicting the effect of glyphosate on the community composition. Graphical abstract: Image 1 Highlights: The effect of nitrogen and glyphosate in a simulated field margin ecosystem. The plant community composition was inferred using model-based ordination. Significant effects of nitrogen and glyphosate on plant community composition. Nitrogen and glyphosate enforced the effect of each other.